Sex-specific anatomical variation of circle of Willis arteries - Phebe J. Groenheide; Iris N. Vos; Robin Bülow; Irene C. van der Schaaf; Birgitta K. Velthuis; Ynte M. Ruigrok (NeuroImage)
Background: Anatomical variations in the circle of Willis (CoW) arteries are common and can affect hemodynamic stress, thereby influencing the risk of cerebrovascular pathology. Previous studies have suggested sex differences in CoW anatomy, but findings vary due to limited study population size and different measurement methods. This study aims to investigate sex differences in artery diameters, anatomical variants and bifurcation angles of the CoW using a large population cohort and semi-automatic measurements. Methods: Sex-specific CoW anatomical variations were assessed using Magnetic Resonance Angiography (MRA) scans of 1,052 individuals without intracranial vascular abnormalities. Diameters and bifurcation angles of large CoW arteries (>1.2 mm) were measured with a semi-automatic tool. Diameters of smaller anterior communicating artery (Acom) and posterior communicating arteries (Pcoms) and the anatomical variants of the CoW were determined manually. Generalized Linear Models (GLMs) and logistic regression models with adjustments for covariates were used to compare anatomical variations between sexes. Results: Men exhibited larger diameters in all semi-automatically measured CoW arteries. A complete anterior CoW was more prevalent in men than women, while there was no difference for the posterior CoW. Aplasia/hypoplasia of the Acom was more prevalent in women. Aplasia/hypoplasia of one Pcom was more common in women, while aplasia/hypoplasia of both Pcoms was more common in men. No sex differences were found in CoW bifurcation angles and in the occurrence of fetal-type posterior cerebral arteries. Conclusion: This study identified significant CoW differences in artery diameters and anatomical variants between sexes, while bifurcation angles between arteries were comparable. Future research should investigate the association between these sex-specific CoW variations and cerebrovascular pathology.